Circulating IL-1β, IL-17, and IP-10 as Potential Predictors of Hepatitis B Virus Infection Prognosis - Zhenzhen Su; Jie Chen; Junlong Zhang; Yunfei An; Yun Liao; Xiaojuan Wu; Chuanmin Tao; Lanlan Wang; Bei Cai (Journal of Immunology Research)
Circulating cytokines and chemokines play critical roles in hepatitis B virus (HBV) infection. Here, we explored the effects of proinflammatory and anti-inflammatory effector molecules on HBV progression, e antigen seroconversion, and liver function. Our results showed that circulating interleukin (IL)-17 may be helpful in HBV spontaneous clearance [odds ratio OR=1.468, 95%confidence interval CI=1.080–1.995, P=0.014] and protective against HBV-related hepatoma development (OR=0.933, 95%CI=0.910–0.957, P<0.001). IL-1β negatively affected HBV clearance (OR=0.052, 95%CI=0.005–0.534, P=0.013). In patients with chronic hepatitis B, interferon-γ-inducible protein-10 (IP-10) levels significantly increased in the group of abnormal liver function (P=0.006). Furthermore, positive correlations of IP-10 with alanine aminotransferase and aspartate aminotransferase levels were observed (rs=0.546 and 0.644, respectively; P<0.001). In conclusion, inflammatory cytokines and chemokines may be a “double-edged sword” for HBV clearance and progression. Further exploration of the roles of IL-17, IL-1β, and IP-10 in chronic HBV infection is needed.